(untitled) (Academia Journal of Medicine, 2019)
Background: Diabetes Mellitus (DM) as a metabolic disorder of multiple etiology, characterized by chronic hyperglycaemia with disturbances of carbohydrate, protein and fat metabolism. The present study was conducted to evaluate serum uric acid as a risk factor for micro- vascular complications of diabetes mellitus. Subjects and Methods: The present study was conducted on 84 patients with type II diabetes mellitus of both genders. 10 ml of blood was obtained for assessment of blood glucose and uric acid level. Results: Age group 40-60 years had 46, 60-80 years had 25 and >80 years had 13 patients. Hyperuricemia was positive in 56 and negative in 28. The difference was significant (P< 0.05). Out of 56 patients with hypertension, 42 had high and 14 had low serum uric acid level. Out of 28 patients who had not hypertension, 18 had high serum uric acid and 10 had low. The difference was significant (P< 0.05). Among 48 patients who had stroke, 28 had high serum uric acid and 20 had low uric acid. The difference was significant (P< 0.05). Conclusion: Elevated serum uric acid levels in type 2 diabetes mellitus cause more micro vascular and macro vascular complications.